Education of humanism: a model of axiological improvement of teachers of the third cycle of primary school - Brooks Fuentes, Hilda Rosa (Transformación, 2025)
Objective: The study aims at devising a model of for teacher’s improvement on the contents and methodology of value education, particularly on humanism. Methods: Analysis-synthesis, induction-deduction, modeling, the structural-functional systemic method, documentary analysis and bibliographic reviewing techniques were used. Results: A theoretical construction that synthesizes knowledge and procedures contextualized in an axiological improvement model, which favors the performance of teachers of the third cycle of the Primary Education Level for the education of the value of humanism. Conclusion: The improvement process with an axiological approach in the education of the value of humanism for Primary Education is essentially based on the organization, coherence and unity of the theoretical and methodological contents so that the teacher of the third cycle achieves the appropriation of knowledge and procedures, transfers their knowledge to their educational practice and enhances their preparation for their performance.